1.
你会了
2.让x=tanx
则lim(secx-1)/secx(1-cosx^2)=lim(secx-1)/secx(1-1/secx^2)=lim(secx-1)/(secx-1/secx)=
lim(secx-1)/(secx+1)(secx-1)/secx=limsecx/(secx+1)=1/2
3.应该有公式我忘了
4.dy=e^x*sin^2x+e^x*2sinx
5.f'=e^(-2x)+x*(-2)*e^(-2x)
f''=-2e^(-2x)-2(x*(-2)*e^(-2x)
)=-2e^(-2x)-4x*e^(-2x)
6.y'=2x*e^(x^2)*cos[e^(x^2)]
7.
同时对y求导得:
1=-sinx+2y'cosy
y'=(1+sinx)/2cosy
8.用换底公式:S-xde^(-x)=-xe^(-x)+Se^(-x)dx=-xe^(-x)-e^(-x)
9.设u=/x,
x=u^2
dx=2udu
原函数得S2cosudu=2sinu
=
2sin/x
/x代表根号下x
10.直接吧dx换成dsinx
原式=Se^(sinx)dsinx=e^(sinx)带入数值=e-1